Determinação de fatores associados à presença de fluxo biliar e à sobrevida após a realização da portoenterostomia de Kasai em crianças com atresia biliar - Thais Costa Nascentes Queiroz (2017)
Introduction: Biliary atresia (BA) is the main cause of obstructive jaundice in the first three months of life and the most frequent reason for pediatric liver transplants. Prognosis is directly related to reestablishment of biliary flow and disappearance of jaundice. Objectives: To evaluate prognostic factors associated with the presence of biliary flow and survival after the surgery. To evaluate histological findings in patients with BA, particularly progression of fibrosis, comparing diagnostic hepatic biopsies DHB to surgical hepatic biopsies (SHB). Patients and Methods: The study included patients diagnosed with AB at Hospital das Clínicas UFMG from 1979 to 2016. The sample was nonprobabilistic and composed of 172 BA patients who underwent portoenterostomy. Out of those, 117 were included in the analysis of factors associated with biliary flow, emphasizing on histology. Those who had both DHB and SHB, 51 patients, were included in histologic analysis of fibrosis progression. Two pathologists blindly reviewed biopsies and Metavir and Ishak scores were used to compare samples. Investigation of intervenient factors for biliary flow was obtained using uni- and multivariate analysis through logistic regression. Kaplan-Meier curves and Cox model were used to evaluate survival rates. Results: Median time between biopsies for histologic analysis of fibrosis progression was eight days. Cirrhosis was more frequent in SHB than in DHB both for Metavir (p=0.006) and Ishak (p=0.016) scores. Metavir score increased by one or more points in 29/51 (56.9%) and, in patients with progression of fibrosis, hepatic cirrhosis was diagnosed in 11/29 (37.9%). Median age at surgery was 81 days and this clinical variable was significantly associated with the presence of biliary flow after Kasai portoenterostomy. Regarding the patients submitted surgery, 71/117 (60,7%) were less than 90 days old and 39/117 (33,3%) obtained biliary drainage. Multivariate analysis showed that age at surgery (p=0.035, OR 2.49 [IC95% 1.07; 5.79]) and giant cell transformation (p=0.004, OR 0.25 [IC95% 0.10; 0.64]) reached the final logistic model for prediction of no biliary flow. Survival rate analysis showed that absence of biliary flow (p<0.0001), age above 90 days of life (p=0.035) and biliary atresia with associated structural malformation (BASM) (p<0.0001) are associated to death or need for liver transplant. Multivariate analysis found significant association between lower survival rates with native liver and absence of biliary flow (p=0.004, OR 0.25 [IC95% 0.10; 0.64]) and presence of BASM (p=0.014 HR:2.16 [IC95% 1.17; 3.99]). Conclusion: Most children with BA already have hepatic fibrosis at diagnosis and its progression is swift. Presence of cirrhosis is related to age at surgery, which points to its importance in disease evolution. Age of over 90 days of life at surgery was identified as an independent risk factor for absence of biliary flow. Furthermore, presence of biliary flow and absence of BASM are fundamental variables for higher transplant-free survival rates.